Hong Kong - Stein, R. Conrad (Chicago : Childrens Press, 1985)
Examines the land, people, history, economy, and cultural life of this busy, crowded, prosperous manufacturing and trading center, a citadel of capitalism on the doorstep of the largest Communist country on earth.
Includes index.
7.6
5-8
Keywords: Hong Kong -- Juvenile literature; Hong Kong; Hong Kong